Advantages and Disadvantages of Online Accounting Education in Universities in Terms of Covid-19 (Research Papers, 2023)
The purpose of this publication is to explore and outline the advantages and disadvantages of online accounting education in the context of an emergency epidemic situation. The defined goal implies the implementation of the following tasks: study of the accounting education process in higher schools; carrying out a comparative analysis of the {~~on-site~>onsite~~} form of training and online training. Scientific methods were used in the research process, such as: comparative analysis, synthesis, historical approach, induction. As a result of the research, guidelines are presented for overcoming the identified shortcomings in online learning.
Keywords: Education; Accounting; Digitization